Environmental framework of coastal plain estuaries - Nelson, Bruce W. (Geological Society of America, 1972)
"Based on presentations at the Symposium on Estuaries, 18th annual meeting of the Southeastern Section, the Geological Society of America, Columbia, South Carolina, April 10 and 11, 1969."Includes bibliographies.